Interventional pulmonology procedures: an update - Gompelmann, Daniela; Eberhardt, Ralf; Herth, Felix (Panminerva medica, 2013)
Bronchoscopy is the most important tool in diagnosis of respiratory diseases, but also provides therapeutic options in various disorders. Besides hemoptysis, airway stenoses are a frequent indication for therapeutic bronchoscopy interventions. Thereby, a broad spectrum of endoscopic techniques including electrocautery, argon plasma coagulation, laser treatment, cryosurgery and stent implantation is available. In the last decade, development of new endoscopic modalities provides also treatment of patients with chronic obstructive pulmonary disease and uncontrolled asthma.
Gesehen am 18.02.2020